LARANGAN PERKAWINAN ANTARA SEPUPU SEJAJAR DI MASYARAKAT ADAT DAYAK KENINJAL DESA BINA JAYA KECAMATAN TANAH PINOH KABUPATEN MELAWI - NIM. A1011201004, STEPANUS JERRY (Jurnal Fatwa Hukum, 2024)
ABSTARCTPROHIBITION OF MARRIAGES BETWEEN EQUAL COUSINS IN DAYAK KENINJAL INDIGENOUS COMMUNITY OF BINA JAYA VILLAGE TANAH PINOH DISTRICT MELAWI REGENCY Marriage customs are an important event in the lives of the Dayak Keninjal indigenous people. Marriage is a holy and sacred thing to establish a life-long relationship until death do us part, so there are customary prohibitions when carrying out a marriage which can be seen in the family tree. The prohibition on marriage between equal cousins is a marriage that is related by blood, this is considered taboo or malicious because it does not respect the ancestors and hurts the hearts of indigenous people. Marriage customs in Bina Jaya Village, Tanah Pinoh District, Melawi Regency have been passed down from generation to generation. As time went by, the Dayak Keninjal Traditional Marriage experienced a shift in the regulations related to the Prohibition of Married Cousins. One of them is the customary fine, the amount of which has been determined and can be reduced depending on the agreement. Then several objects that are requirements for marriage, such as knives, jugs, cloth, can be replaced with money according to the value of the objects that are conditions for marriage. In this research the author formulates the problem of "What are the legal consequences if a marriage occurs between equal cousins in the Dayak Keninjal Indigenous Community in Bina Jaya Village, Tanah Pinoh District, Melawi Regency?" This research aims to obtain data and information about the prohibition of marriages between equal cousins in the Dayak Keninjal Indigenous Community, Bina Jaya Village, Tanah Pinoh District, Melawi Regency, to reveal the factors that cause marriages between equal cousins in the Dayak Keninjal indigenous community, to reveal the legal consequences if a marriage occurs. between equal cousins in the Dayak Keninjal indigenous community and to reveal the efforts of traditional elders in prohibiting the practice of marriage between equal cousins in the Dayak Keninjal indigenous community, Bina Jaya Village, Tanah Pinoh District, Melawi Regency. This research uses empirical legal research methods, namely by describing the conditions at the time of the research and analyzing them to draw conclusions. The nature of this research is descriptive. The data analysis used for research is qualitative data analysis. Based on the research results, it can be concluded that the implementation of sanctions against marriages of equal cousins in Bina Jaya Village, Tanah Pinoh District, Melawi Regency will be subject to sanctions against couples who carry out the Prohibition of Marriages of Equal Cousins. Factors that cause first-cousin marriages are mutual love, lack of education, economics and relationships outside of marriage. The legal consequences for couples who marry equal cousins are subject to Cabuh customary sanctions, namely in the form of customary fines that have been determined by customary functionaries. Efforts made by functionaries to prohibit the practice of marriage between equal cousins in the Dayak Keninjal Indigenous Community, Bina Jaya Village, Tanah Pinoh District, Melawi Regency by providing education to the community, especially the younger generation. Keywords: Prohibition, Customary Sanctions, Parallel CousinsABSTRAKLARANGAN PERKAWINAN ANTARA SEPUPU SEJAJAR DI MASYARAKAT ADAT DAYAK KENINJAL DESA BINA JAYA KECAMATAN TANAH PINOH KABUPATEN MELAWI Adat Perkawinan merupakan peristiwa penting bagi kehidupan masyarakat adat Dayak Keninjal. Perkawinan hal yang suci dan sakral untuk menjalin hubungan sehidup semati sampai maut memisahkan sehingga ada larangan larangan adat ketika akan melaksanakan perkawinan yang dilihat dalam silsilah keluarga. Larangan perkawinan sepupu sejajar merupakan perkawinan yang masih satu ikatan darah hal ini dianggap tabu atau mali karena tidak menghormati leluhur nenek moyang dan mencederai hati masyarakat adat. Adat perkawinan di Desa Bina Jaya Kecamatan Tanah Pinoh Kabupaten Melawi di wariskan secara turun menurun. Seiring berjalannya waktu, Perkawinan Adat Dayak Keninjal mengalami pergeseran yang mengatur terkait Larangan Perkawinan Sepupu Sejajar. Salah satunya adalah denda adat yang telah di tentunkan jumlahnya bisa dikurangi tergantung kesepakatan. Kemudian beberapa benda yang menjadi persyaratan dalam perkawinan seperti pisau, kendi, kain dapat diganti dengan uang sesuai dengan nilai benda yang menjadi syarat perkawinan. Dalam penelitian ini penulis merumuskan masalah tentang "Bagaimana Akibat Hukum Apabila Terjadi Perkawinan Antara Sepupu Sejajar Di Masyarakat Adat Dayak Keninjal Di Desa Bina Jaya Kecamatan Tanah Pinoh Kabupaten Melawi?" Penelitian ini bertujuan untuk mendapatkan data dan informasi tentang larangan Perkawinan Antara Sepupu Sejajar Di Masyarakat Adat Dayak Keninjal Desa Bina Jaya Kecamatan Tanah Pinoh Kabupaten Melawi, untuk mengungkapkan faktor penyebab terjadinya Perkawinan antara sepupu sejajar pada masyarakat adat Dayak Keninjal, untuk mengungkapkan akibat hukum apabila terjadi Perkawinan antara sepupu sejajar pada masyarakat adat Dayak Keninjal dan untuk mengungkapkan upaya dari tetua adat dalam melarang praktek perkawinan antara sepupu sejajar di masyarakat adat Dayak Keninjal Desa Bina Jaya Kecamatan Tanah Pinoh Kabupaten Melawi. Penelitian ini menggunakan metode penelitian hukum empiris yaitu dengan menggambarkan keadan pada waktu penelitian dan menganalisa hingga mengambil kesimpulan. Sifat penelitian ini adalah deskriptif. Analisa data yang digunakan untuk penelitian adalah analisa data kualitatif.Berdasarkan hasil penelitian dapat disimpulkan bahwa pelaksanaan penerapan sanksi terhadap perkawinan sepupu sejajar di Desa Bina Jaya Kecamatan Tanah Pinoh Kabupaten Melawi akan dikenakan sanksi kepada pasangan yang melakukan Larangan Perkawinan Sepupu Sejajar. Faktor penyebab terjadinya perkawinan sepupu sejajar adalah faktor saling cinta, kurangnya Pendidikan dan edukasi, ekonomi dan hubungan di luar pernikahan. Akibat hukum bagi pasangan yang melakukan perkawinan sepupu sejajar dikenakan sanksi adat Cabuh yaitu berupa denda adat yang sudah ditentukan oleh fungsionaris adat. Upaya yang dilakukan Fungsionaris dalam melarang praktek Perkawinan Antara Sepupu Sejajar Di Masyarakat Adat Dayak Keninjal Desa Bina Jaya Kecamatan Tanah Pinoh Kabupaten Melawi dengan melakukan penyuluhan kepada masyarakat terutama generasi muda. Kata Kunci : Larangan, Sanksi Adat, Sepupu Sejajar